PENGARUH HUMAN CAPITAL, MARKETING CAPABILITY, TERHADAP FINANCIAL PERFORMANCE DAN MARKET VALUE (Studi Kasus pada Perusahaan Sektor Property dan Real Estate) - Rebecca Christine; Sarce Elsye Hatane (Business Accounting Review, 2016)
This study aims to determine the direct effect of significant human capital, marketing capability, company age and size of the company financial performance and market value on companies in the property sector and real estate. This research shaped kualtitatif research, where data obtained through the financial statements published by the company. The data obtained were then processed using SPSS software. The results of this study revealed a positive and significant relationship of human capital and financial performance, and a lack of correlation between marketing capabilities, company age, company size and financial performance, and also a lack of correlation between human capital, marketing capabilities, and the company of age against market value, however a significant positive relationship between company size of the market value of the companies in the property sector and real estate.